Gestión logística en el local “el palacio del Ruliman” en la ciudad de ventanas en el periodo 2023. - Coronado Peñafiel, Diego Orlando (2024)
This study focuses on the analysis of the logistics management of the “El Palacio del Rulimán” premises, located in the city of Ventanas, during the period 2023, its main purpose is to evaluate the processes in the supply chain, identifying critical points that affect the operational efficiency of the business and proposing corrective measures that optimize its operation. The first aspect will be to identify the current logistics processes and the internal factors that affect them by applying the EFI matrix, a tool that allows evaluating strengths and weaknesses within logistics management. Subsequently, a Logistics Process Map will be established, in order to visualize and analyze the stages of the supply chain, identifying errors and areas for improvement in key activities such as storage, distribution and inventory management. Finally, corrective measures will be proposed based on the results of the diagnosis carried out, these actions will be aimed at improving the coordination of logistics processes, increasing operational efficiency and guaranteeing more effective supply, thus achieving better business performance. The scope of this research lies in its ability to generate both practical and theoretical contributions in the field of logistics management, benefiting “El Palacio del Rulimán” and serving as a reference for other businesses in the commercial sector. This approach allows the specific needs of the company to be met, promoting its competitive and sustainable development in the local market.